Pengaruh Transparansi, Akuntabilitas, dan Responsibilitas Pengelolaan Keuangan Sekolah terhadap Kinerja Guru pada Sekolah Dasar di Plemahan-Kediri - Amelia Candra Murti; Rohmawati Kusumaningtias (Jurnal Riset Akuntansi, 2025)
This research aims to determine the effect of transparency, accountability and responsibility in school financial management on teacher performance in Plemahan-Kediri. The research sample was elementary school teachers in the Plemahan-Kediri sub-district. The research method used in this research is a quantitative method with sampling using proportional random sampling technique, data testing using SPSS 26 software which is analyzed using multiple regression tests. The results of the research conducted show that transparency and accountability have a negative effect on teacher performance. Meanwhile, responsibility has a positive effect on the performance of elementary school teachers in Plemahan-Kediri.